The Learning Process in the Epistemology of Medical Information - Clancey, W. J. (Methods of Information in Medicine, 1995)
Progress in the past few decades in representing medical knowledge, along with the availability of low-cost, powerful workstation computers, has increased interest in encoding all medical records in electronic form. But despite the advantages of legibility, access, and automated performance reviews, computerization may also restrict what can be recorded and rigidify health care interactions with patients. Balancing the beneficial and negative effects requires an understanding of medical practice, especially the difference between human knowledge and today’s computer programs. Human perceptual and conceptual capabilities bring an aspect of improvisation and reinterpretation to every human action, which in general computers today cannot replicate. Designers of medical record systems must consider the creative process by which descriptions are generated by people, as well as the collaborative process by which descriptions of past work are reinterpreted for guiding future decisions. This paper provides a framework for understanding these issues, illustrated by design opportunities.
Keywords: Human Learning; Medical Vocabulary; Objectivism; Holistic Analysis; Medical Practice